2007
DOI: 10.1093/ndt/gfm421
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the clinical efficacy and safety of sevelamer in dialysis patients

Abstract: Compared with calcium-based phosphate binders, use of sevelamer in dialysis patients is associated with similar to slightly higher phosphate levels, similar calcium phosphate product, and slightly lower serum calcium levels. There was no evidence that sevelamer reduced all-cause mortality, cardiovascular mortality, the frequency of symptomatic bone disease or health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 48 publications
1
63
0
8
Order By: Relevance
“…This study was followed by a meta-analysis that reported no difference in all-cause mortality between the 2 groups. 21 …”
Section: Sevelamer Hydrochloridementioning
confidence: 99%
“…This study was followed by a meta-analysis that reported no difference in all-cause mortality between the 2 groups. 21 …”
Section: Sevelamer Hydrochloridementioning
confidence: 99%
“…Neste subgrupo de pacientes, sevelamer foi usado em lugar de quelantes contendo cálcio, mesmo em situações de hipocalcemia. O fato de não existirem evidências suficientes mostrando benefício na redução de mortalidade, hospitalização ou melhora da qualidade de vida associadas ao uso do hidrocloreto de sevelamer apoia a necessidade da reavaliação da prescrição dos quelantes de fósforo observada no presente estudo 11 . Tonelli et al realizaram uma meta-análise que incluiu dez ensaios clínicos randomizados totalizando 3.000 pacientes em diálise que utilizaram sevelamer ou um dos quelantes à base de cálcio 11 .…”
Section: Discussionunclassified
“…In contrast to these studies, a systematic review comparing calcium-based binders to sevelamer failed to identify a mortality reduction associated with this therapy (30). The more recent CARE-2 study demonstrated similar progression of coronary calcification in 203 dialysis patients randomized to either sevelamer or calcium acetate, although the study was limited to 1 yr (31).…”
Section: Potential Therapiesmentioning
confidence: 98%